IMF Staff papers : Volume 7 No. 1. (IMF Staff Papers; IMF Staff Papers, 1959)
This paper describes the connection between the need for financial statistics as an aid to monetary and financial policy. The essential unifying element between statistics and policy is, of course, theory-a coherent set of assumptions regarding the behavior of the economy. These assumptions will indicate how the economy is expected to respond to changes of particular variables on which policy action concentrates. The accounts of the money and banking and financial system can provide a large part of the required financing statistics in a highly reliable form. In all economies a large part of borrowing and lending is indirect. Among the financial institutions, the banking system stands out, not merely because of its relative magnitude but because of its ability to create its own liabilities. Both banks and life insurance companies grant credit; that is not where the difference lies. A simple model of the economy can be built on the basis of injections of income that can be observed from available statistics.